Methods of Teaching Turkology (Journal of Educational Sciences, 2021)
The article reveals the history and features of the formation of the science of Turkology. It also tells about the current state of Turkology. Turkology originates in linguistics and continues in such areas of science as folklore, literature, history, and ethnography. It is in these disciplines that we analyze the heights of Turkology achieved today. For Turkology, each place has an important meaning and signifi- cance. The analysis of scientific works on Turkic studies raises topical issues in the field of science. The most pressing issue of Turkology is the analysis of the nature of the interdisciplinary complex. Works on Turkic studies are described. It is quite obvious that the most important things that modern Turkic stud- ies need are moving. The reason for the emergence of Turkic studies is a rational understanding of the unity of the Turkic peoples. It covers the main features that enable the Turkic language to become the most important language. It became clear that Türkology can exist through the Türkic language. It was concluded that the solution of the most pressing problems in the science of Turkology is directly related to the restoration of the Turkic people. Methods of induction, deduction, system analysis and empirical methods were used in the study.Key words: Turkology, coordination, oriental studies, modernization, philosophy, folklore, literature, ethnography, linguistics, global, antihistoricism.